2012
DOI: 10.1016/j.jarmac.2012.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Showups versus lineups: An evaluation using ROC analysis.

Abstract: Showups (a one-person identification) were compared to both simultaneous and sequential lineups that varied in lineup fairness and the position of the suspect in the lineup. We reanalyzed data from a study by Gronlund, Carlson, Dailey, and Goodsell (2009), which included simultaneous and sequential lineups, and using the same stimuli and procedures, collected new data using showup identifications. Performance was compared using ROC analysis, which is superior to traditional measures such as correct and false i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
131
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(164 citation statements)
references
References 37 publications
23
131
0
Order By: Relevance
“…Recently, Receiver Operator Characteristic (ROC) analysis was introduced in the adult eyewitness memory literature (Gronlund et al, 2012: Mickes, Flowe, & Wixted, 2012 to address these issues. ROC analysis does not rely on any distribution assumptions, and allows one to examine memory sensitivity across age groups, regardless of whether responding is liberal or conservative.…”
Section: Roc Approach To Examining Age-related Differences In Id Accumentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Receiver Operator Characteristic (ROC) analysis was introduced in the adult eyewitness memory literature (Gronlund et al, 2012: Mickes, Flowe, & Wixted, 2012 to address these issues. ROC analysis does not rely on any distribution assumptions, and allows one to examine memory sensitivity across age groups, regardless of whether responding is liberal or conservative.…”
Section: Roc Approach To Examining Age-related Differences In Id Accumentioning
confidence: 99%
“…Support for the late maturation hypothesis in the criminal lineup identification literature, however, has been equivocal, because of the analytic approach that has been used to examine age-related changes in identification performance. Recently, Receiver Operator Characteristics (ROC) analysis was applied for the first time in the adult eyewitness memory literature to examine whether memory sensitivity differs across different types of lineup tests (Gronlund et al 2012;Mickes, Flowe, & Wixted, 2012). ROC analysis allows for the separation of memory sensitivity from response bias in the analysis of recognition data.…”
mentioning
confidence: 99%
“…Gronlund and colleagues replicated and extended Mickes et al's (2012) results (Gronlund et al, 2012). First, they did not find evidence of sequential superiority.…”
mentioning
confidence: 70%
“…ROC analysis presents the cumulative hit and false alarm rate at each level of witness confidence, accumulating from the highest to the lowest confidence level. From the results we can ascertain the lineup procedure that produces the higher ROC; the higher the curve, the greater the discrimination accuracy afforded by the lineup procedure (for a review of ROC analysis applied to lineups, see Gronlund et al, 2012;Mickes et al, 2012). Mickes et al (2012) conducted two studies, and found evidence that discrimination accuracy was greater in the simultaneous condition in Study 1a, whereas discrimination accuracy did not differ across procedures in Study 1b.…”
mentioning
confidence: 99%
“…Instead, over the years, the debate had been whether there was a sequential superiority effect (because it tended to yield a higher diagnosticity ratio) or whether the two procedures were diagnostically equivalent. Now, multiple ROC studies of simultaneous vs. sequential lineups have been published, and they all show evidence of a simultaneous superiority effect, though the effect is not always significant (Carlson & Carlson, 2014;Dobolyi & Dodson, 2013;Gronlund et al, 2012;Mickes et al, 2012). To date, no ROC study has shown the slightest hint of a sequential superiority effect.…”
Section: Simultaneous Vs Sequential Lineups In the Labmentioning
confidence: 99%